An Analysis of Conversational Implicatures during the Debate Between 2012 Candidates of DKI Jakarta Governor - Dony Wijaya Kusumah (Universitas Pendidikan Indonesia (UPI), 2015)
This study seeks to investigate the conversational implicatures during the debate between 2012 candidates of Jakarta Governor and to identify which maxims the candidates failed to observe, also to identify what implicatures that are attained from the violated maxims. Data were taken from DKI Jakarta governor candidates debate aired on Metro TV on August 18, 2012. Data relevant to implicatures were marked and numbered. The data were analyzed by classifying conversations with maxim violations. The results show that the governor candidates commit flouting towards Grice's (1975) maxims. The maxim the candidates violated the most was relevance maxim. Furthermore, the flouting occurs due to several factors comprising lack of knowledge, insufficient evidence, and avoidance answering questions in purpose. However, even though some violations were done, some of the candidates were able to use sentences or utterances in compliance with the cooperative principles since only half of the data that are violated.Keywords: Conversational Implicatures, Debate, Grice's Maxims, Maxims Flouting